HUMAN RESOURCE DEVELOPMENT POLICY INTERVENTION IN THE CONTEXT OF CULTURAL HARMONY - Silo, Akbar (International Journal of Social Science, 2025)
This article aims to analyze the effectiveness of human resource development (HRD) policies in Papua by considering aspects of local cultural harmony. This research is motivated by the many failures of the implementation of HR management techniques and practices adopted directly from developed countries without adjustment to the local cultural context. Through a qualitative literature study approach, the author reviewed literature from figures such as Hofstede, Robbins, and Mendonca & Kanungo to understand cultural incompatibility as a major obstacle in HR development. The results showed that Papuan cultural values such as collectivism, high power hierarchy, and preference for short-term orientation, contradict the universalistic HR management model that emphasizes individualism and efficiency. It was emphasized that effective management practices must be adapted to local cultural characteristics, including paternalistic leadership approaches, community empowerment based on traditional values, and the use of honest and open communication styles. Intervention strategies rooted in the local cultural context have been shown to increase the effectiveness of HR development programs. The discussion confirms that the success of HRD policy interventions in Papua is highly dependent on the ability to ensure harmony between local cultural norms and modern management techniques. Therefore, strategic adjustments that are context-specific.